Colon and rectal surgery : anorectal operations - Wexner, Steven D.,; Fleshman, James. (Master techniques in general surgery, 2012)
"Master Techniques in General Surgery: Colon and Rectal Surgery: Anorectal Operations is a volume in a series that presents common and advanced procedures in the major subspecialities of general surgery. The series is overseen by Josef F. Fischer, MD, editor of the classic two-volume reference Mastery of Surgery. Master Techniques in General Surgery: Colon and Rectal Surgery: Anorectal Operations is written by acknowledged master surgeons, emphasizes surgical procedures, and is lavishly illustrated with original full-color drawings. The contributors fully explain their preferred techniques in step-by-step, thoroughly illustrated detail, assess indications and contraindications, offer guidelines on preoperative planning, and discuss outcomes, complications, and follow-up. Coverage includes hemorrhoidectomies, anal fistula and sphincter procedures, procedures for perineal prolapse and excision of rectal carcinoma, among others. A companion website will offer fully searchable content of the book, an image bank, and procedural videos"--Provided by publisher.